Kumbheshwar Mahadev Temple Complex - Temples of India Project Team (Jio Institute, 2024)
Seen here is the south-facing elevation of the main central shrine of the Kumbheshwar Mahadev Temple complex. According to its plan, the temple consists of a mukhamandapa (front porch), mandapa (pillared hall), antarala (vestibule and antechamber) and a garbhagriha (sanctum sanctorum). The mukhamandapa facing east-west has not survived, barring its plinth. A row of kutas (aedicules) is visible above the main shrine which indicates that the temple must have been adorned with a shekahri shikhara (multi-spired superstructure). The bhadra (central projection) on the south elevation had a sculpture of Tripurantaka Shiva.